EFEKTIVITAS KEGIATAN MUROJAAH BERBANTU AUDIO DALAM MENINGKATKAN DAYA HAFAL SANTRI - Syahila Nazua Ritonga; Zaini Dahlan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of audiovisual-assisted recitationactivities in improving memorization skills of students at the Tahfidz Baitul Qur'anBinjai Islamic Boarding School and the obstacles encountered. This researchmethod uses a qualitative approach with field research. The respondents in thisstudy were all 16 male students at the Tahfidz Baitul Qur'an Binjai IslamicBoarding School. The results of this study indicate that audiovisual assistance iseffective in improving memorization skills of students. Audiovisual assistance withradio is very helpful for students to remember quickly, because the stimulus oflistening helps children in improving their memory. Therefore, the author providesconstructive suggestions for future research to conduct research in Islamicboarding schools that have existed for 20 years. Also, the Tahfidz Baitul Qur'anBinjai Islamic Boarding School Foundation can implement jasus (spies) from itsselected students to monitor and report students who commit prohibitions anderrors.